Investigating how outdoor environmental education programmes in South Africa respond to the needs of visually impaired learners via inclusive practices - Eksteen, Hendrik Christiaan (Rhodes University, Faculty of Education, Department of Education, 2019)
Outdoor environmental education programmes in South Africa are conducted at campsites and centres owned by the government, non-profit organisations and private owners. People suffering from impairments are often disabled by society because of their handicap. More than three percent (3%) of young people in South Africa aged between 10 "“ 19 years are disabled. This study investigates the status of inclusion of outdoor environmental education programmes for disabled young people; what is offered and what practices are working in the industry in South Africa. It also investigates barriers to inclusion. Though many disabilities have been identified, visual impairment is the focus of the study. This study also looks at what more can be done from an Ecological Systems Theory of Human Development point of view and investigates what underlying mechanisms influence the inclusion of visually impaired individuals in outdoor environmental education programmes in South Africa. What is done and what is not done to promote inclusion for visually impaired learners in these programmes is also investigated. This study aims to answer the question; What is the current status quo concerning the inclusion of visually impaired learners in outdoor environmental learning programmes in environmental education centres and campsites in South Africa? An initial focus group conducted informally prior to the study, helped me to understand the context. In this study, key-interviews and questionnaires were used as research tools. I also ran a photo narrative project throughout the research project which was used as a participatory activity and provided further insight into practices. Inductive, abductive and retroductive analysis approaches were used to identify emerging themes, and I applied method triangulation using all research tools in order to address the research questions. Some of the most important findings are that: "¢ There are many barriers, some intrinsic others extrinsic, that hinder inclusion of visually impaired individuals in outdoor environmental education programmes in South Africa. "¢ Although there are many things done in the industry to promote inclusion, there is much more that could be done. "¢ The visually impaired individual him/herself influences inclusivity in outdoor environmental education programmes. "¢ Interactions and influences in the mesosystem (between different microsystems and ecosystems) have an impact on the inclusivity of visually impaired individuals in outdoor environmental education programmes. "¢ Dispositions of people have an impact on the inclusion of visually impaired individuals in outdoor environmental education programmes. "¢ The diversity of generative mechanisms (drivers to events), that interact at the level of the real, influence the inclusion of visually impaired individuals in outdoor environmental education programmes. Disability/impairment is a much-neglected area of environmental education research in South Africa. This study has contributed scholarship to this area and has also identified possible further areas of study in creating awareness, creating an opportunity to reflect on practices, and finding possible solutions to the barriers of exclusion.
Keywords: Children with visual disabilities -- Education -- South Africa; Outdoor education -- South Africa; Environmental education -- South Africa; Outdoor recreation for children with disabilities -- South Africa; Inclusive education -- South Africa